KEBIJAKAN OTONOMI SEKOLAH DAN OTONOMI BIROKRASI PENDIDIKAN KABUPATEN/KOTA - Fauzi, Anis (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2010)
If we want to be honest, as a matter of fact, there are many regions that are not ready to receive various authorities in the context of the religion autonomy yet, including in carrying aut the authority on education sector. The reasons for his are (a) insufficient human resourse, (b) unavailabel means and infrastructures, (c) the very low provincial budget, (d) the lack of mentality toward changes, (e) being nervous and afraid toward renewal or innovative efforts. To be bureaucratic elite is dilemmatic and confusing. On the one hand, one has to works hard to serve the complex and hard problen of the society; on the other hand, the regulations of the district head are financial monitoring which is becoming stricter and stricter as well as the multiinterpretation between the organizer and the law enforcer apparatus. Realization of decentralization in the school management needs the readiness from all supporting elemnts in the region. There are, at least, four elements that schould be prepared in order that the realization of decentralization succeed: (1) Law and regulation that regulate decentralization of education from distric or provincial level until the instituation level, (2) the devloment of the region capability, (3) creating the startegy of unit which is in charge of making education planning, (4) the readiness of society in receiving and helping to create the conducive milieu for realization of the decentralization. Keywords: school autonomy, autonomy of education bureaucracy, district / city